2017
DOI: 10.12659/msm.902340
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Infective Endocarditis: Outcomes and Predictors of Mortality in 360 Consecutive Patients

Abstract: BackgroundA retrospective analysis was conducted of the early and long-term outcomes after surgery for infective endocarditis (IE).Material/MethodsWe included 360 patients with IE operated upon between 1993 and 2012. The primary endpoint was overall cumulative postoperative survival at 30 days. Secondary endpoints were early postoperative outcomes and complication rates. Factors associated with 30-day mortality were analyzed.ResultsMean age was 58.7±14.7 years and 26.9% (n=97) were female. The mean follow-up w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 40 publications
5
42
0
5
Order By: Relevance
“…28 Acute renal failure can occur in about 30% of patients who underwent cardiac surgery, especially in heart failure, diabetes mellitus, and geriatric patients and associated with 30-days mortality post-cardiac surgery. 12,17 Our findings showed that acute renal failure appeared in 30% of IE patients although not considered statistically significant due to the small sample population. In a larger study, renal insufficiency increased mortality 1.6-fold higher in IE patients, although postoperative renal failure complications appeared in only 7.2% of subjects and average care in the ICU for more than 7 days.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…28 Acute renal failure can occur in about 30% of patients who underwent cardiac surgery, especially in heart failure, diabetes mellitus, and geriatric patients and associated with 30-days mortality post-cardiac surgery. 12,17 Our findings showed that acute renal failure appeared in 30% of IE patients although not considered statistically significant due to the small sample population. In a larger study, renal insufficiency increased mortality 1.6-fold higher in IE patients, although postoperative renal failure complications appeared in only 7.2% of subjects and average care in the ICU for more than 7 days.…”
Section: Discussionmentioning
confidence: 58%
“…Our study showed that IE patients had 5-fold higher risk to experience a prolonged ICU stay more than 6 days which occurred in 86.6% of IE patients. Pato et al 4 and Farag et al 17 also showed that IE patients who underwent mitral valve surgery have an increased risk of prolonged stay in the ICU with an average treatment period more than 10 days. Another study with larger samples also showed similar results with an average length of stay in the ICU of almost 8 days, and it related to the advanced classifications of the New York Heart Association (NYHA III or NYHA IV) before surgery and is usually associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Approximately 12% of patients with IE require a permanent pacemaker (PPM) to be inserted postoperatively. 4,5 The etiology of heart block in patients with IE undergoing surgery is likely multifactorial, including both infective destruction and surgical debridement of valvular tissue and the intrinsic conduction system. Heart block may also be transient due to trauma and edema from surgical manipulation in close proximity to the conduction system.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients who undergo cardiac surgery for IE, the reported rate of PPM implantation postoperatively is about 12%, which is consistent with our incidence of 11%. 4,5 Conversely, in the absence of IE, the rate of postoperative PPM is low at 6%. 8,9 The Postoperative prolonged PR >200, N (%) 7 (50) 22 (24) .01…”
mentioning
confidence: 99%